A Thorough Systematic Review of The Impact of Educational Interventions On The Quality of Life For Pregnant Women Experiencing Nausea And Vomiting - Mutia Juliana (International Medical Journal Corp. Ltd, 2024)
Background: Hyperemesis gravidarum (HG) is the primary cause of early pregnancy hospitalization and sick leave, causing significant financial costs. Improper management can result in negative pregnancy outcomes and lower women's quality of life. Methods: The systematic review included research articles assessing the impact of educational intervention on women with NVP's quality of life, published from 2000 to 2023. Result: The review explores the impact of educational interventions on the quality of life of pregnant women in Iran, Taiwan, Norway, and the UK. The studies, conducted in hospitals, health centers, and social media, measured QOL using tools like NVPQOL, SF36.v2, EQ-5D, and QoLS. Five of the seven RCT studies reported a significant effect. Conclusion: The study explores the impact of educational interventions on pregnant women experiencing nausea and vomiting related-pregnancy (NVP) and their quality of life. It found that exercise education and strong support networks can improve QOL. However, factors like pain, depression, low education, younger age, and lack of a partner can negatively affect QOL.